My hospital doc com memoir Dr. Non - Mohd Noor Awang (Dya Planner Sdn Bhd, 2017)
Myhospitaldoc.com is an imaginary story house, the first of its kind which revealed the untold true stories of exciting incidences happening in the hospital set-up in Malaysia. Myhospitaldoc.com begins with the life story of its creator as an under privileged kampong boy, the survival, determination and his challenges journey of becoming a successful oral and facial reconstructive surgeon. Myhospitaldoc.com unveils many exciting and sensational true stories of life in a hospital set up based on author's personal experiences and observations as a senior consultant and also incidences relaxes by staffs, patients and visitors. This books also highlighted success and failure stories of selected cases who suffered from illness whose experiences can be shared by all. At the same time the text is enriched with valuable information, guardians and tips for keeping the body fit, healthy and look younger as well as measure to prevent illnesses.